Synthesis and characterisation of Li-modified g-C3N4 - Jasni, Normawati; Iqbal, Anwar; Ahmad, Mohammad Norazmi; Pauzi, Hariy; Hussain, M. Hazwan (Elsevier Ltd., 2021)
Graphitic carbon nitride (g-C3N4) is of great interest in photolysis. However, g-C3N4 suffers from a fast recombination rate of photogenerated electron and hole (e-/h+ ) pairs. It is hypothesised that surface modification of g-C3N4 with alkali metals is able to suppress the recombination rate of photogenerated e-/h+ pairs. Hence, in the present research, a series of lithium modified g-C3N4 (xLi/g-C3N4 (x = 2.7, 5.0 and 9.0 wt%)) nanocomposites were synthesised by impregnating g-C3N4 with LiOH. The synthesised nanocomposites were characterised using x-ray powder diffraction (XRD), inductive coupled plasma mass spectroscopy (ICP-MS), scanning electron microscopy (SEM), uv–vis diffuse reflectance spectroscopy (DRS UV–Vis), high resolution electron microscopy (HRTEM), photoluminescence (PL), Fourier transform infrared (FT-IR) and thermogravimetric (TGA) analyses. The TGA analysis showed that the thermal stability of the Li/g-C3N4 decreased compared to g-C3N4 due to the enlarged interlayer distance over g-C3N4. The XRD analysis indicates that a larger distance of the in-planar structure motif of g-C3N4 downshifted the (0 0 2) diffraction line of the g-C3N4 from 27.60 to 26.83 and weakened its intensity after doping. Increasing the Li+ concentration transformed the Li/g-C3N4 into a disordered graphite nanocomposite. The IR peak intensity at 2174 cm1 associated with the defect terminal –C-N increased when the Li+ concentration was increased, indicating that the incorporation of Li+ reduced the degree of melamine condensation and formed g-C3N4 with more defect sites. The HRTEM images showed that the g-C3N4 thin nanosheet structure became uneven and wrinkled after doping. Rock-like particles were observed when the Li+ concentration exceeds 5 wt% Li/g-C3N4. Similar rock-like and plate-like particles with voids were observable in the nanocomposites’ SEM images. The UV–Vis analysis indicates that Li+ doping reduced visible light sensitivity of the Li/g-C3N4 nanocomposites compared to g-C3N4, possibly due to the distortion of the g-C3N4 planar structure. The PL analysis indicates that the photogenerated recombination rate e-/h+ pairs were suppressed even though the sensitivity towards visible light decreased.